PENINGKATAN PROSES DAN HASIL BELAJAR IPA MENGGUNAKAN MODEL THINK PAIR SHARE - Tri Wiyoko; Dian Listia Ningrum; Aldino Aldino; Elvima Nofrianni; Reni Guswita (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research started from the problem of the lack of attention of students during the learning process, and the low level of mastery of students on the subject matter of Natural Sciences. This resulted in low process and learning outcomes for students. This study aims to describe the improvement of the process and learning outcomes of students in class V SD Negeri 60/II Muara Bungo. This research is a Classroom Action Research (CAR) with qualitative and quantitative approaches. The subjects of this study were students of class V SD Negeri 60/II Muara Bungo, totaling 12 people. the implementation of this research consists of two cycles conducted by the researcher. Each cycle consists of planning activities, and implementing actions accompanied by reflection observations in each cycle. This research was conducted in the second semester of the 2021/2022 academic year at SD Negeri 60/II Muara Bungo. The research data were collected through observation, documentation, and test results. The results showed that the use of the think pair share model of students could improve the process and learning outcomes of students. This can be seen from the increase in the learning process of students, in the first cycle it reached an average of 64.22% in the sufficient category, and in the second cycle, it increased to 86,21% in the good category. The increase in student learning outcomes in the first cycle reached an average of 58.88% in the poor category and the second cycle reached an average of 83.33% in the good category.